Estudio de sistemas acuíferos de origen fluvio lacustre, como base para el análisis de la dinámica hidrogeológica en áreas de baja pendiente. Caso de estudio en la Cuenca media del Río Bogotá-Sector Parcelas Cota y Suba Occidental - Chaparro Gordillo, Sara Eulalia (Universidad Antonio Nariño, 2024)
The study is developed in the metropolitan area between the municipality of Cota and the western area of Suba - Fontanar of the city of Bogotá, and includes the hydrogeological characterization by components, for the identification and/or definition of the possible interconnection between aquifer systems associated with Fluvio-Lacustrine Deposits and the hydro-dynamic system of the Bogotá River, using methodologies of compilation, identification and validation at a general level according to each component to be developed, achieving an integration of its results in a Conceptual Hydrogeological Model.